Farhangī faqer - Yūn, Muḥammad Ismāʿīl (Yūn Kultūrī Yūn, 2008)
Collected articles of the author on Afghanistan's civilization in 21st century
Includes bibliographical references
Keywords: Paschtu; Literatur; Kultur